Written and unwritten numbers in Plato - Cattanei, Elisabetta (Revista Archai, 2011)
In this article, we try and light on some elements which compose the relationship between “written” and “unwritten” mathematics in Plato. In order to do this, we confront a series of indirect reports provided, among others, by Aristotle, in order to recover as much as we can of a general picture of these elements, always starting from the basis provided by Plato’s Texts.